Diagnostic evaluation of a prediction nomogram for preeclampsia - Alegría-Guerrero, Raúl (2019)
Objective. Determine the study of the diagnostic test of the prediction nomogram for the risk of preeclampsia. Material and method. A nested case-control analytical observational study and validation of the proposed prediction index was performed with the design of a nomogram. It was performed at the Guillermo Almenara Irigoyen-EsSalud Hospital, Lima-Peru, and Fetal Medicine Unit. Participated asymptomatic pregnant patients of the Almenara-EsSalud Healthcare Network between the first or second trimester of pregnancy that developed or not at the end of the follow-up severe preeclampsia. The clinical, laboratory and Doppler predictors of the uterine arteries were evaluated. The data obtained were analyzed under a multivariate binary logistic regression model to construct the prediction equation and the prediction nomogram. In addition, the ROC curve analysis was performed. Results. The prediction nomogram includes clinical, laboratory and Doppler parameters. It has an area under the curve (AROC) of 0,82, p <0,001. The proposed nomogram qualifies risks in high, intermediate and low. It reaches a sensitivity of 82,2%, a specificity of 75,1%, a VPN 86,6% and a PPV of 98,8%. Conclusions: The nomogram to predictor of risk of severe preeclampsia proposed preeclampsia predicts the development with high sensitivity can be used in clinical practice.